Sustaining the traditional wood craft for industrial production by the master woodcarvers of peninsular Malaysia - Kamaruddin, Zumahiran; Zakariya, Khalilah; Nazuki, Siti Najwa (2017)
The art of Malay traditional wood carving has been popularly practiced in the past centuries and continuously implemented by the present generation of woodcarvers in Malaysia. In the current context, a desire for a modern industrial production of wood craft by local people as an alternative choice, has given some positive impact on the market value for Malaysian traditional craft. This paper discusses the production of the wood carving as national craft by two master woodcarvers from the northeastern region of Peninsular Malaysia, namely Wan Mustafa Wan Su and Noorhaiza Nordin. Their works and opinions that served as inferential evidences were obtained through face-to-face interviews that were conducted within an informal environment. The interviews focused on the aspect of fabrication of wood carving with particular emphasis on creative use of carving techniques and design for domestic application. Observation and photographic documentation of their works were necessary measures to complement the interviews. Hence, examination on the carvings produced by the woodcarvers which exemplifies their distinctive craftsmanship is also addressed in this paper. The study found that the most profound works produced by them are wood paneling for houses and mosques that reflect their self and regional identity. Also most of their works are inspired and derived from nature which signifies their strong preferences to the application of floral design. This implies that apart from Islamic religious belief, creativity and innovation has become the most influencing factors that govern their craftsmanship. In addition, the physical and practical values of the carvings extracted from the past traditions are still in tact in their works. This study concludes that traditional craftsmanship along with additional values including artistic and design skills that enrich the products of the master woodcarvers from this region should be sustained for future development of woodcraft industry in Malaysia.